2022
DOI: 10.1093/eurpub/ckac118
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 lockdown on air pollution in Europe and North America: a systematic review

Abstract: Background Multiple studies report reductions in air pollution associated with COVID-19 lockdowns. Methods We performed a systematic review of the changes observed in hazardous air pollutants known or suspected to be harmful to health, including nitrogen dioxide (NO2), nitrogen oxides (NOx), carbon monoxide (CO), sulfur dioxide (SO2), ozone (O3) and particulate matter (PM). We searched PubMed and Web of Science for studies re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…68 Based on the results of a systematic review by Bakola et al (2022), several air pollutants, including NO 2 , NO, PM2.5, PM10, CO, carbon dioxide (CO 2 ), benzene, black carbon, and air quality index (AQI)) related to the quarantine of COVID-19, showed a significant and strong decrease. 69…”
Section: Findings and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…68 Based on the results of a systematic review by Bakola et al (2022), several air pollutants, including NO 2 , NO, PM2.5, PM10, CO, carbon dioxide (CO 2 ), benzene, black carbon, and air quality index (AQI)) related to the quarantine of COVID-19, showed a significant and strong decrease. 69…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Studies have reported a reduction in pollutant concentrations during quarantine compared to the same period in previous years and even more robustly with historical data of more than 5 years. 68 Based on the results of a systematic review by Bakola et al (2022), several air pollutants, including NO 2 , NO, PM2.5, PM10, CO, carbon dioxide (CO 2 ), benzene, black carbon, and air quality index (AQI)) related to the quarantine of COVID-19, showed a significant and strong decrease. 69 According to the results of a systematic review study by Faridi et al, 70 in 2021, quarantine measures related to the COVID-19 epidemic significantly reduced the concentration of PM2.5, NO 2 , PM10, SO 2 , and CO globally.…”
mentioning
confidence: 99%
See 3 more Smart Citations